Determinat of Tax Aggressiveness in Banking Companies at 2021-2022 Period - Anggraeni , Annisa Fitri; Roswinna, Winna; Yulianti, Maria Lusiana; Putri, Kartika Pratiwi; Aisyah, Taty Siti (Dinasti Publisher, 2025)
This study aims to analyze the influence of liquidity, earnings management, independent commissioners, and executive compensation of tax aggressiveness. The population in the study is a Banking Company Registered in Indonesia Stock Exchange in the period 2021-2022. The sample is taken by using purposive sampling method, where the banking company that issued the financial statements, did not move sector, listed its shares and did not have negative profit during the period 2021-2022. The design in the study is hypothesis testing, where the sample consists of 60 samples. Data processing using multiple linear regression with eviews 13.The results of this study found that liquidity, earnings management and independent komisais affect tax aggressiveness, while executive compensation does not affect the aggressiveness of taxes. Based on total adjusted R-Square results prove that liquidity, earnings management, independent commissionist, and executive compensation only affect 65.8%, while 24.2% is influenced by other variable not tested in this research.